Exercise-Induced Asthma Symptoms and Nighttime Asthma: Are They Similar to AHR?. (18th October 2009) - Backer, V.; Rasmussen, L. M.
Abstract : Background . Asthma experienced during exercise and during the night is based on the presence of airway hyperresponsiveness (AHR). The aim of the present study was to examine whether AHR is a predictor of exercise-induced asthma (EIA) and nighttime symptoms. Material . We included 793 asthmatics subjects with symptoms and a positive asthma test. Results . Mean (SD) FEV1 was 93% (15), 71% had rhinitis, and 62% had atopy. Both EIA and nighttime symptoms were associated with AHR; however, when including other factors of importance in a multivariate analysis, log RDR was eliminated, whereas FEV1% pred (P < .001 ), smoking (P < .05 ), atopy (P < .001 ), sex (P < .001 ), and treatment (P < .01 ) were associated with having EIA while dyspnoea (P < .001 ), cough (P < .001 ), and eosinophils (P < .01 ) were associated with frequent night symptoms. The risk of having nighttime awakenings due to asthma was more than twofold higher among those with EIA symptoms than among those without symptoms (OR (CI95%) 2.77 (2.0–3.8) (P < .001 )). In Conclusion . EIA and night symptoms are associated with AHR, but other factors of importance eliminated this close association. Night asthma is more closely associated with airway inflammation than AHR.